Kurikulum Pendidikan Seni Budaya yang Ideal bagi Peserta Didik di Masa Depan - Ardipal Ardipal (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2010)
The purpose of education is to develop all the basic potentials possessed by the learners. To develop the potentials of learners, the professionalism of educators should be improved. Therefore, improvement of professional skills of educators should be directed to the standard of competency. Learning the art of the ideal culture should be in accordance with the demands of the curriculum. The curriculum should be equipped with a supplemental materials and textbooks that are relevant as a reference for art educators in carrying out the duties and responsibilities of his profession, so that learners can cope with the changes, expectation and challenges in the future.. Key words: Curriculum, ideal art and culture